Determinants of stillbirths in Katsina, Nigeria: a hospital-based study - Bello M. Suleiman; H.M. Ibrahim; N. Abdulkarim (Pediatric Reports, 2015)
Every year, about 3 million stillbirths occur globally, almost a third occurring during the intra-partum period. Almost all stillbirths (98%) occur in low and middle income countries, with Nigeria having the third largest burden. The aim of this study was to determine the stillbirth rate and its determinants in the Federal Medical Centre Katsina, located in north western Nigeria. This study was a retrospective review of all deliveries conducted between 1st March 2010 and 31st December 2012 in Federal Medical Centre Katsina. Data were extracted from labor room and theatre records, and patient folders. Cases were matched with controls by booking status. The privacy and confidentiality of information retrieved from cases and controls was also ensured by anonymizing the data retrieved. No conflict of interest was identified. The data was analyzed with SPSS 20. During the period under review, there were 6628 deliveries, out of which 331 of the products were stillborn. The stillbirth rate was 46.9±3.6 per 1000 deliveries. Determinants of stillbirths were antepartum hemorrhage, hypertensive disorders of pregnancy, uterine rupture, low birth weight and congenital fetal malformations. The study highlighted the poor perinatal health in the study population.